Costs of the Supervision, Performance Assessment and Recognition Strategy (SPARS) for improving medicines management in Nepal - Anika Ruisch; Ganesh Khatiwada; Anup Bastola; Christian Suharlim; Birna Trap (Taylor & Francis Group, 2024)
Background Nepal implemented a pilot of the Supervision, Performance Assessment, and Recognition Strategy (SPARS) program aimed to increase health workers' ability to manage medicines through on- the-job training and support from a new cadre of Medicines Management Supervisors (MMS). This study aims to assess the implementation costs.Methods Data from the SPARS central database and facilities was analysed to assess the total cost of the SPARS pilot including 293 public health facilities from 12 districts of 3 provinces, from May 2022 until July 2023. We estimated the number of health facilities to achieve a successful performance status, defined as a SPARS score ≥ 18.75 out of 25 (75%) and estimated the cost per facility to reach a successful score.Results In total, 293 facilities received 838 visits, performed by 48 MMS for an estimated total cost of $226,531. 124 facilities (44.3%) reached a score of 18.75 points after two or more visits. On average, it costs $1827 USD per facility to reach a successful SPARS score.Conclusion This study assesses the costs of implementing SPARS in 12 districts in Nepal. These findings can provide insights into further scaling up SPARS in Nepal or in other countries.